Gambling, Status Anxiety and Inter-Generational Social Mobility: Findings from the Mass Observation Archive. (April 2020) - Casey, Emma
This article is located within sociological research exploring the subjective experiences and emotional consequences of social mobility in the UK. It adds to recent attempts to examine the role of everyday cultural practices in making sense of journeys of upward mobility. The article draws on these theoretical advancements and applies them to a case study of everyday gambling practices using qualitative data ( N = 24) collected from the Mass Observation Archive. The article represents one of the first attempts to examine the connections between social mobility and gambling. It draws on sociological research that explores the cultural as well as the economic underpinnings of social mobility and connects this to research examining the inter-relationships between gambling and class. By doing so, it aims to present a novel theoretical approach to the study of gambling as everyday consumer practice; one which can be understood alongside broader cultural and structural inequalities of class.